Effect of Different Dialysis Membranes on Protein Loss During Hemodialysis - Mir, Abdul Wahab; Raja, Khalid Mahmood; Azam, Malik Nadeem; Arshad, Abdul Rehman; Tahir, Taleah; ., Salahuddin (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the loss of proteins with high and low flux hemodialysis membranes.Study Design: Cross-sectional analytical study.Place and Duration of Study: Department of Nephrology, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Nov 2019 to Feb 2020.Methodology: This study was conducted on patients with end-stage renal disease on maintenance haemodialysis. We excluded patients on haemodialysis for less than one month, those with poor compliance to hemodialysis, those undergoing hemodialysis for less than four hours per session and unwilling patients. Patients were divided into two groups: one was dialyzed with high flux membranes, whereas low flux membranes were used for the other group. Dialysate samples were collected during the first hour and then during the last hour of each haemodialysis session to estimate protein losses in each group.Results: Data were recorded during 133 hemodialysis sessions, the patients underwent. There were 22 patients, including 12 (54.55%) males, having a mean age of 46.45±13.99 years. Most patients (17, 77.27%) were on twice-a-week dialysis, whereas the rest were dialyzed thrice weekly. Protein loss was 0.45± 0.23g/L with low flux membranes and 1.20±0.60g/L with high flux membranes. This difference was statistically significant (p=